Case study: Stardew Valley a technological game as tool to enrich english classes - MUNIZ, Jhessy Eduarda Soares (2023)
This article aims to present a case study with two first year high school students for the use of the Stardew Valley game in English learning. The theoretical framework is based on the principles of digital culture (PRENSKY, 2001, 2010; PALFREY; GASSER, 2011; ZOLTÁN, 2001; BRASIL, 2016; among others) as a way of integrating it into the classroom environment in the Brazilian context, in which students can consciously appropriate games and technologies. Regarding the methodology, this research is characterized as a qualitative case study (GERRING, 2019) and uses an interview as a research instrument. The data were generated in a sequence of classes given in the English language discipline at the Escola Estadual de Ensino Médio Melvin Jones (EEEMMJ). The results show that the Stardew Valley game can contribute to innovative learning for students, when leaving, for example, traditional teaching practices, as technologies allow students to connect to their everyday world outside the walls of the school. In addition, the teacher needs to adapt to the digital world and help the student to be autonomous in their learning. Therefore, it is worth mentioning that pedagogical innovation through games needs to be taught, to help the student from his needs.